THE ROLE OF BUSINESS LEGALITY, HALAL LABELING AND PROMOTION IN INCREASING THE COMPETITIVENESS OF MSME PRODUCTS IN KWALA SERAPUH VILLAGE, LANGKAT - Erwansyah, Erwansyah; Yanti, Eli Delvi; Wahyono, Teguh; Ninda, Via Vio (Proceeding International Seminar of Islamic Studies, 2024)
MSMEs are one of the important economic sectors that play a role in the Indonesian economy. However, MSMEs still face various challenges, one of which is increasingly fierce competition with imported products. Therefore, MSMEs need to improve their competitiveness in order to survive and develop. This study aims to analyze the role of business legality, halal labeling, and promotion in increasing the competitiveness of MSME products in Kwala Serapuh Village, Langkat. This research uses a survey method with 50 respondents, namely MSME actors in Kwala Serapuh Village. The results showed that business legality, halal labeling, and promotion have a significant role in increasing the competitiveness of MSME products in Kwala Serapuh Village. Business legality can increase consumer confidence in MSME products, thereby increasing their competitiveness. Halal labeling can improve the image of MSME products in the eyes of consumers, thereby increasing their competitiveness. Promotion can increase consumer awareness of MSME products, thereby increasing their competitiveness. Based on the results of this study, it is recommended that MSMEs in Kwala Serapuh Village can improve the legality of their business, obtain halal labeling, and actively promote to increase the competitiveness of their products.